Actual Management of Anterior Calyceal Diverticular Calculi: A Challenging Flexible Retrograde Endoscopic Approach - Ali Barki; Anouar El Moudane (Case Reports in Urology)
Calyceal diverticula is a cavity that communicates with the collecting system through a narrow isthmus of the kidney. The incidence of the formation of stones in calyceal diverticula is 10-50%. This paper reports three cases of two females and one male who presented with calyceal diverticular calculi; the patients have been, arbitrarily, selected between August and February 2019 at the urology department of our university hospital. A minimally invasive treatment includes extracorporeal lithotripsy (ESWL), and F-URS (flexible ureteroscopy) was performed. We report this case series.